Decision support systems - Grad, Janez (Informatica (Ljubljana), 1987)
In this paper we describe and analyze Decision Support Systems (DSS) as a class of Information Systems (IS). We first state a definition of DSS, explainits relation to management information system and the objectives of DSS. Afterwards, our discussions are devoted to: (i) The iterative design for DSS. (ii) The current computer and information technology that supports DSS. (iii) The current status and application of DSS for marketing analysis, sales forecasting, financial planning, transportation, etc... (iv) The future trends in DSS. We give a broad overview of the expected development and use of DSS, in particular the further impact of technology and the necessary changes in organizations and decision processes.
Keywords: computer graphics; computer science; decision support system; fourth-generation languages; informacijski sistemi; informatika; information science; information system; interaktivni pristop; iterative approach; jeziki četrte generacije; prototipni pristop; računalniška grafika; računalništvo; sistemi za podporo odločanja; software prototypes